2023
DOI: 10.1002/cncr.34917
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ expectations, preferences, and recall of germline findings in a childhood cancer precision medicine trial

Abstract: BackgroundGermline genome sequencing in childhood cancer precision medicine trials may reveal pathogenic or likely pathogenic variants in cancer predisposition genes in more than 10% of children. These findings can have implications for diagnosis, treatment, and the child’s and family’s future cancer risk. Understanding parents’ perspectives of germline genome sequencing is critical to successful clinical implementation.MethodsA total of 182 parents of 144 children (<18 years of age) with poor‐prognosis can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 45 publications
2
5
0
Order By: Relevance
“…McGill et al 5 . found that parents are interested in the disclosure of VUSs, consistent with other recent studies 21 .…”
supporting
confidence: 82%
See 4 more Smart Citations
“…McGill et al 5 . found that parents are interested in the disclosure of VUSs, consistent with other recent studies 21 .…”
supporting
confidence: 82%
“…Postdisclosure counseling should also include education about cascade testing for family members (when appropriate), syndrome and patient support/ advocacy groups, and outlining plans for surveillance and cancer risk reduction. Importantly, McGill et al 5 also found that a third of parents of children with negative germline results misperceived that their child had clinically relevant germline findings, which supports informational needs for those with negative results as well. 14 Such misperceptions risk unnecessary distress and/or anxiety regarding future cancer risk, surveillance and medical follow-up, and genetic testing for family members.…”
mentioning
confidence: 95%
See 3 more Smart Citations